Oxidative Transformations of Some Azinyl Sulfides - A. Petrič; B. Stanovnik; M. Tišler (CHIMIA)
Some mixed azinyl sulfides were prepared as multidentate model compounds in order to study their oxidative transformations. It could be observed that hydrogen peroxide attacked the sulfide bond or caused N-oxidation of the pyridine ring, but the predominant process was hydrolytic cleavage of the sulfide bond.